Analisis Sentimen Terhadap Program Kampanye Desak Anies Di X Menggunakan Naïve Bayes - Dimas Arya; Ilka Zufria (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Information technology provides many influences including political, economic, artistic, cultural, social and educational. In 2023 the number of internet users in Indonesia will reach 215.63 million. This increase shows how important social media platforms like X are in public discussions. All attention is focused on political campaigns ahead of the Indonesian presidential election in 2024. This research was conducted to determine public sentiment towards two-way campaigns such as "Desak Anies" in X. Using the Naive Bayes algorithm, researchers divided public sentiment into 3 categories, namely positive, negative, and neutral. This shows public opinion and the effectiveness of campaign strategies. This research analyzes public opinion as much as 1401 comment data. The Naive Bayes algorithm is known to be very good at classifying text, followed by text pre-processing which is useful for cleaning text data so that it can be processed further. Next, TF-IDF is used to extract features. Using the Naive Bayes algorithm, sentiment classification shows the distribution of public opinion towards the "Desak Anies" campaign. The results provide useful suggestions for Amin's team in improving their strategy. The classification results show an accuracy of 90%, precision of 96%, recall of 93%, and F1-score of 95%. With more positive comments than neutral and negative comments.